EFEKTIVITAS SISTEM SINGLE TRUCK IDENTIFICATION DATA (STID) UNTUK MENGURANGI KEMACETAN ARUS TRUK DI DALAM WILAYAH PELABUHAN TANJUNG PRIOK - Inaayah Prada Banowati; Fahrani Aulia Rahmi, Abel Jackson Revano, Kayla Azizia Patricia Litiloli (Jurnal Salome : Multidisipliner Keilmuan, 2024)
Single Truck Identification Data (STID) is a single identification system for truck vehicles that has a unique number that is accepted nationally or regionally. STID aims to make it easier to identify vehicles and make it easier to monitor and regulate truck traffic at the port. This research focuses on analyzing the application of STID, with the main aim of finding out its effectiveness in overcoming the problem of truck traffic congestion in the Tanjung Priok Port area. The method used is a qualitative approach with descriptive analysis, and data was obtained through library research. The research results show that the application of STID to overcome congestion is considered successful, assessed through three main dimensions: goal achievement, integration, and adaptation.